2010
DOI: 10.2337/db09-1881
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid Receptor Stimulation Impairs Mitochondrial Biogenesis in Mouse White Adipose Tissue, Muscle, and Liver

Abstract: OBJECTIVECannabinoid type 1 (CB1) receptor is involved in whole-body and cellular energy metabolism. We asked whether CB1 receptor stimulation was able to decrease mitochondrial biogenesis in different metabolically active tissues of obese high-fat diet (HFD)-fed mice.RESEARCH DESIGN AND METHODSThe effects of selective CB1 agonist arachidonyl-2-chloroethanolamide (ACEA) and endocannabinoids anandamide and 2-arachidonoylglycerol on endothelial nitric oxide synthase (eNOS) expression were examined, as were mitoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
99
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 140 publications
(108 citation statements)
references
References 53 publications
6
99
1
2
Order By: Relevance
“…In addition, the Cannabis sativa (marijuana)-derived cannabinoid ⌬9-THC, and the synthetic cannabinoid HU210 (a mixed CB1R/CB2R agonist), have also been shown to impair mitochondrial respiratory function by reducing oxygen consumption and mitochondrial membrane potential (4). Moreover, both AEA and 2-AG have been reported to downregulate the expression of genes implicated in mitochondrial biogenesis such as PGC-1␣ as well as reduce mitochondrial DNA amount and oxygen consumption in mouse white adipocytes (142).…”
Section: Regulation Of Mitochondrial Function By the Ecsmentioning
confidence: 99%
“…In addition, the Cannabis sativa (marijuana)-derived cannabinoid ⌬9-THC, and the synthetic cannabinoid HU210 (a mixed CB1R/CB2R agonist), have also been shown to impair mitochondrial respiratory function by reducing oxygen consumption and mitochondrial membrane potential (4). Moreover, both AEA and 2-AG have been reported to downregulate the expression of genes implicated in mitochondrial biogenesis such as PGC-1␣ as well as reduce mitochondrial DNA amount and oxygen consumption in mouse white adipocytes (142).…”
Section: Regulation Of Mitochondrial Function By the Ecsmentioning
confidence: 99%
“…Activation of the cannabinoid receptor type-1 (CB1) stimulates adipogenesis and lipogenesis, leading to impaired mitochondrial function in diet-induced obesity (DIO) (20,23,24). CB1 activation in mouse and human WAT reduces mitochondrial mass and function by downregulation of PPARγ coactivator 1α (Ppargc1a), while genetic and pharmacological blockade of CB1 function increases mitochondrial biogenesis by enhancing Ppargc1a expression (24,25). Accordingly, body weight loss induced by chronic administration of CB1 antagonists is largely due to increased energy expenditure (EE) and consequent activation of lipolysis and fatty acid oxidation (21,(26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%
“…A recent in vivo proteomics analysis in mice WAT and BAT shows that there are quantitative and qualitative differences between the mitochondria from both tissues: BAT mitochondria are more similar to muscle mitochondria and WAT mitochondria express proteins associated with anabolic functions and proteins involved in the degradation of xenobiotics (Forner et al, 2009). Recent studies suggest that mitochondrial biogenesis and metabolism are implicated in the regulation of various processes in WAT, such as pre-adipocytes proliferation, adipogenesis, carbohydrate and lipid metabolism, adipocyte de-differentiation, TAG accumulation and acquirement of BATlike characteristics (De Pauw et al, 2009;Forner et al, 2009;Tedesco et al, 2010;Bordicchia et al, 2012;Koponen et al, 2012) and impaired mitochondrial biogenesis contributes to the onset of obesity and related metabolic disorders, such as insulin resistance (Tedesco et al, 2010).WAT mitochondrial biogenesis in mice is correlated with the up-regulation of genes involved in fatty acid oxidation and mitochondrial electron transport activity, boosting WAT catabolism (Granneman et al, 2005). Indeed, it was demonstrated that mitochondrial proliferation and remodeling are enhanced in 3T3-L1 cells during adipogenesis and the use of insulin sensitizers, such as rosiglitazone, leads to significant alterations in mitochondrial morphology and augmentation of the expression of several mitochondrial proteins (Wilson-Fritch et al, 2003).…”
Section: Wat Mitochondria In Obesity and Inflammationmentioning
confidence: 99%